THE EFFECT OF LOCAL GOVERNMENT SPENDING ON EDUCATION SECTOR AND GDP ON HDI IN INDONESIA - Nur Ramadini Tria Wafa; Saparuddin Mukhtar; Harya Kuncara Wiralaga (International Research of Multidisciplinary Analysis, 2023)
Human resource-based economic development is one of the priorities implemented in Indonesia because Indonesia has a significant population potential. Indonesia ranks among the five lowest countries in its human development index in ASEAN. This study aims to determine the influence of government spending in the education sector and GDP Regional in increasing HDI in Indonesia in 2015-2018. This study used multiple regression analysis panel data with a total sample of 26 provinces in Indonesia with 104 observation units. This study found that local government spending in the education sector had a positive and significant effect on HDI and GDP Regional also had a positive and significant influence in increasing HDI in Indonesia in 2015-2018